2017
DOI: 10.48550/arxiv.1708.08413
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BRITEning up the Be Phenomenon

D. Baade,
Th. Rivinius,
A. Pigulski
et al.

Abstract: Observations of 25 Ori much expand the picture derived of other earlytype Be stars with BRITE and SMEI. Two instead of one difference frequencies rule the variability: (a) The lower one, 0.0129 c/d, is the frequency of events with full amplitudes of 100-200 mmag which may signal mass loss possibly driven by the higher one, 0.1777 c/d. (b) Much of the entire power spectrum is a tightly woven network of combination frequencies: (i) Below 0.25 c/d, numerous frequencies are difference frequencies. (ii) Many freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…This was confirmed by Pápics et al (2017) in the same data. In the early-type Be star 25 Ori, Baade et al (2017b, an extended version of this work with additional BRITE and revised SMEI observations is in preparation) tentatively identified an extremely rich pattern of grouped combination frequencies.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…This was confirmed by Pápics et al (2017) in the same data. In the early-type Be star 25 Ori, Baade et al (2017b, an extended version of this work with additional BRITE and revised SMEI observations is in preparation) tentatively identified an extremely rich pattern of grouped combination frequencies.…”
Section: Introductionmentioning
confidence: 83%
“…During the monitoring period with Kepler, also KIC 11971405 underwent some small outbursts. As Baade et al (2017b) showed, the spacing in time of some of these events can be related to difference frequencies of some NRP modes with the highest amplitudes. Such coupling had previously been found in BRITE, Kepler, and CoRoT observations of several early-type Be stars (Baade et al 2016;Rivinius et al 2016;Baade et al 2017b, Rivinius et al, in prep.).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations